Emerging Technological Risk Underpinning the Risk of Technology Innovation - Anderson, Stuart; Felici, Massimo (Springer London : Imprint: Springer, 2012)
Classes of socio-technical hazards allow a characterization of the risk in technology innovation and clarify the mechanisms underpinning emergent technological risk. Emerging Technological Risk provides an interdisciplinary account of risk in socio-technical systems including hazards which highlight: ·         How technological risk crosses organizational boundaries, ·         How technological trajectories and evolution develop from resolving tensions emerging between social aspects of organisations and technologies and ·         How social behaviour shapes, and is shaped by, technology. Addressing an audience from a range of academic and professional backgrounds, Emerging Technological Risk is a key source for those who wish to benefit from a detail and methodical exposure to multiple perspectives on technological risk. By providing a synthesis of recent work on risk that captures the complex mechanisms that characterize the emergence of risk in technology innovation, Emerging Technological Risk bridges contributions from many disciplines in order to sustain a fruitful debate. Emerging Technological Risk is one of a series of books developed by the Dependability Interdisciplinary Research Collaboration funded by the UK Engineering and Physical Sciences Research Council.